KOMPETENSI WIRAUSAHA, PEMBINAAN, SERTA LOKASI USAHA PENGARUHNYA TERHADAP KESUKSESAN BERWIRAUSAHA BAGI PELAKU USAHA SKALA MIKRO - Muhamad Rifa’i; Suprihatin Suprihatin; Warter Agustim (J-MACC, 2019)
Success in conducting business activities carried out by small businesses often faced with the many issues faced. These obstacles often make small businesses difficult to develop. This research aims to describe the influence of entrepreneurial competency, coaching and business location to the success of entrepreneurial in small business traders located in the village of Tlogomas Malang. The approach used is quantitative. The results of the study showed that competence has no significant effect on successful business. Coaching variables influence positively but also insignificant to business success. While the location of business affects positively and significantly to the success of the business, but simultaneously competence, coaching, and business locations influence positive and significant to the success of the business.